Reappraisal of waist circumference cutoff value according to general obesity. Issue 1 (December 2016) - Kim, Kyung-Soo; Oh, Hyun-Ju; Choi, Young; Huh, Byung; Kim, Soo-Kyung; Park, Seok; Lee, Eun; Cho, Yong-Wook; Huh, Kap-Bum
Abstract Background Current criterion of waist circumference (WC) for abdominal obesity is not enough to demonstrate characteristics of obese and non-obese populations defined by BMI. The aim of this study was to redefine the cutoff values of WC according to general obesity (BMI ≥ 25 kg/m2 ). Methods The receiver operating characteristic curve analysis was performed to determine cutoff values of WC for predicting atherosclerosis according to BMI in 1, 063 non-diabetic subjects. To validate this new criterion, diabetic patients (n  = 3, 690) were divided into three groups based on the current (WC of 90/80 cm for men/women) and new cutoff values of WC: 1) group with WC below the lowest value of two criteria; 2) intermediate group defined as having a WC between them; and 3) group with WC more than the highest value of them. Results The new cutoff values of WC for predicting atherosclerosis in non-diabetic subjects were 84/76 cm for non-obese men/women, and 93/87 cm for obese men/women, respectively. Of non-obese diabetic patients, the intermediate group (WC 84 ~ 90/76 ~ 80 cm for men/women) was more insulin resistant and showed elevated odds ratio (OR) for having 2 or more metabolic risk factors compared to group with WC below 84/76 cm for men/women [OR 2.48 (95 % CI 1.89–3.25) in men, 2.01 (95% CI 1.45–2.78) in women]. In contrast, among obese diabetic patients, insulin resistance and the likelihood of having 2 or more metabolic risk factors were not different from the intermediate group (WC 90 ~ 93/80 ~ 87 cm for men/women) and group with WC below 90/80 cm for men/women. Conclusions The current universal cutoff values of WC may under- or over-estimate the metabolic risks of intermediate groups. Therefore, the WC criteria for abdominal obesity should be applied differently depending on the BMI.